Managerial Practices in Improving the Quality of Education in Sekolah Indonesia Jeddah - Fifi Nofiaturrahmah; Rukhaini Fitri Rahmawati; Yunis Eka Putra; Mei Ernawati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This research is motivated by the problems faced in Sekolah Indonesia Jeddah (SIJ) on providing quality education for children of Indonesian citizens abroad, including the adaptation of the national curriculum to the local context in Jeddah, limited resources (teachers, facilities, and funding) and differences in students' cultural backgrounds. The purpose of this study was to analyze managerial practices in improving the quality of education in Sekolah Indonesia Jeddah. The method used is qualitative. Data were obtained using observation techniques, interviews, and documentation studies. Subjects in the study consisted of principal, vice principal, teachers and student Guardian. These subjects were selected using purposive sampling techniques. Data analysis techniques start from data collection, data reduction, data presentation, and drawing conclusions. Data validity testing through source triangulation. The results of the study indicate that management practices at SIJ have a significant impact on the quality of education provided. SIJ management practices use an holistic approach. This research emphasizes the need for open management that accepts input from various stakeholders, from curriculum planning to resource management, implementation of educational programs, and periodic evaluation. This research contributes to improving the quality of Indonesian school education abroad.